Sosialisasi Pengawasan Partisipatif “Mengawasi Pemilu dengan Jujur dan Adil : Kita Berpartisipasi!” - Bawaihi; Ibnu Al Rasyid; Desy Noor Hidayah; Najwa Salya Rahmadina; Bahran, S.H, M.H (Interdisciplinary Explorations in Research Journal, 2024)
Free and fair elections are one of the main pillars in maintaining democracy in Indonesia. Community involvement in election monitoring is essential to ensure the integrity and transparency of every stage of the election. integrity and transparency in every stage of the election. This research aims to explore the role of community participation in election monitoring, with a focus on the implementation of the 2024 regional head elections (Pilkada). Through participatory approach, the community is expected to play an active role as a monitor, which not only assists the Election Supervisory Body (Bawaslu) in the monitors, who not only assist the Election Supervisory Body (Bawaslu) in carrying out its duties, but also educate themselves about their rights and carry out their duties, but also educate themselves about their rights and obligations as citizens. obligations as citizens. Socialization activities carried out in various areas, such as in Bagelen District, show the enthusiasm of the community to be involved in election monitoring. involved in election supervision. In the socialization, participants were given knowledge about the monitoring mechanism and how to report suspected violations. With a high awareness of the importance of participatory the importance of participatory supervision, it is hoped that it can prevent fraudulent practices and violations that can harm the democratic process. can harm the democratic process. The results showed that participatory oversight not only improves the quality of elections, but also strengthens popular sovereignty. strengthen people's sovereignty. Therefore, encouraging the active participation of participation in election monitoring is a strategic step to achieve luber (direct, general, free and secret) and jurdil (fair and just) elections. fair). This research recommends the need for more innovative strategies in innovative strategies in involving the community so that election monitoring can run effectively and sustainably. effective and sustainable.